Prejudice against veiled Muslim women: The role of right-wing authoritarianism and intergroup anxiety - Inderasari, Annisa Puspita; Sampe Tondok, Marselius; Yudiarso, Ananta (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2021)
A series of acts of terrorism involving women in various parts of the world, including in Indonesia, allegedly carried out by radical Muslim groups, has strengthened stereotypes and created prejudice against Muslim women who wear the veil. This study aims to explain the role of right-wing authoritarianism (RWA) and intergroup anxiety as antecedents of prejudice against veiled Muslim women. Using a cross-sectional survey design, the study sample (N= 403), domiciled in the city of Surabaya, Indonesia, was selected by accidental sampling. RWA, intergroup anxiety, and prejudice against veiled Muslim women were measured using a questionnaire, and the research hypotheses was analyzed by multiple linear regression. The results show that RWA and intergroup anxiety play a significant role in explaining prejudice against veiled Muslim women (R = .826; R2 = .682; F = 428.68; p < .01), with the relative contributions of RWA and intergroup anxiety being 34% and 66% respectively. The theoretical implication of the research is that RWA and intergroup anxiety act as antecedents of prejudice against veiled Muslim women.